Pengaruh Komitmen Organisasional, Organizational Citizenship Behavior (OCB), Kepemimpinan Trasformasional, Job Insecurity Dan Budaya Organisasi Terhadap Kepuasan Kerja. - Anindita Imam Basri; Samuel Tri Nugroho (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2022)
This study aims to analyze the effect of organizational commitment, Organizational Citizenship Behavior (OCB), transformational leadership, job insecurity and organizational culture on employee job satisfaction. This research was carried out at SuperDazzle, the population in this study were all SuperDazzle employees totaling 110 employees with Non Probability Sampling, sampling technique with purposive sampling method, this type of research used survey method using a quantitative approach. Based on the results of the study using the t test, the results showed that the organizational commitment variable had a significant effect on job satisfaction for employees with a significance value of 0,027 < 0,05, the Organizational Citizenship Behavior (OCB) variable had a significant effect on job satisfaction for employees with a significance value of 0,018 < 0,05, the transformational leadership variable has a significant effect on job satisfaction for employees with a significance value of 0,032 < 0,05, the job insecurity variable has a significant effect on job satisfaction for employees with a significance value of 0,006 < 0,05 and the organizational culture variable has a significant effect on job satisfaction for employees with a significance value of 0,003 < 0,05.